2016
DOI: 10.1124/jpet.115.230748
|View full text |Cite
|
Sign up to set email alerts
|

Off-Target Vascular Effects of Cholesteryl Ester Transfer Protein Inhibitors Involve Redox-Sensitive and Signal Transducer and Activator of Transcription 3-Dependent Pathways

Abstract: Elevated blood pressure was an unexpected outcome in some cholesteryl ester transfer protein (CETP) inhibitor trials, possibly due to vascular effects of these drugs. We investigated whether CETP inhibitors (torcetrapib, dalcetrapib, anacetrapib) influence vascular function and explored the putative underlying molecular mechanisms. Resistance arteries and vascular smooth muscle cells (VSMC) from rats, which lack the CETP gene, were studied. CETP inhibitors increased phenylephrine-stimulated vascular contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Accordingly, Rios et al (43) also found that dalcetrapib has CETP-independent effects. Indeed, they demonstrated that dalcetrapib induces the secretion of aldosterone in mouse adipocytes (43) and increases the vascular contraction of rat mesenteric arteries (44). Thus, it remains possible that dalcetrapib could have an off-target effect that could be species dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Rios et al (43) also found that dalcetrapib has CETP-independent effects. Indeed, they demonstrated that dalcetrapib induces the secretion of aldosterone in mouse adipocytes (43) and increases the vascular contraction of rat mesenteric arteries (44). Thus, it remains possible that dalcetrapib could have an off-target effect that could be species dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on isolated mesenteric artery smooth muscle cells in culture or isolated basilar arteries from young and old mice reveal the importance of T696 phosphorylation in mediating the vascular response to ROS (Rios et al. ; Lubomirov et al. ) and in the pathology of contractile responses of cerebral arteries from hypertensive and prediabetic rats (Abd‐Elrahman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing HDL-C with pharmacotherapy, including cholesteryl ester transfer protein (CETP) inhibitors, did not show protective effects against CVD and mortality [ 15 , 16 , 17 , 18 ]. Among the plausible causes of adverse reactions with CETP inhibitors (torcetrapib and evacetrapib), a slight increase in blood pressure [ 19 , 20 ] and vasoactive effects [ 21 ] were observed and possibly were considered as markers of profound adverse reactions due to neuroendocrine or vasomotor effects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%